Cosmotopia Delineated: Rammohun Roy, William Adam, and the Calcutta Unitarian Committee. Issue 2 (August 2020) - Midgley, Clare
Abstract: This article seeks to establish the value of the concept of cosmotopia to historians of intercultural connections through presenting a case study of the Calcutta Unitarian Committee, which was active between 1821 and 1828. In tandem, it aims to enhance understanding of the origins of one particularly sustained set of intercultural connections: the interfaith network which developed between an influential group of Hindu religious and social reformers, the Brahmo Samaj, and western Unitarian Christians. The article focusses on the collaboration between the two leading figures on the Committee: Rammohun Roy, the renowned founder of the Brahmo Samaj, who is often described as the Father of Modern India; and William Adam, a Scottish Baptist missionary who was condemned as the "second fallen Adam" after his "conversion" to Unitarianism by Rammohun Roy, and who went on to cofound a utopian community in the United States. It explores the Calcutta Unitarian Committee's activities within the cosmopolitan milieu of early colonial Calcutta, and clarifies its role in the emergence of the Brahmo Samaj, in the development of a unique approach to Christian mission among Unitarians, and in laying the foundations of a transnational network whose members were in the vanguard of religious innovation, radical social reform, and debates on the "woman question" in nineteenth-century India, Britain, and the United States. In conclusion, the article draws on the case study to offer some broader reflections on the relationship between utopianism, cosmopolitanism, and colonialism.